Psychosocial outcome in adult men born with hypospadias - Örtqvist, L.; Andersson, M.; Strandqvist, A.; Nordenström, A.; Frisén, L.; Holmdahl, G.; Nordenskjöld, A. (Journal of pediatric urology, 2017)
Hypospadias, which is a surgically treated congenital malformation of the male urethra, may have a negative impact on quality of life. This aspect has previously been subject to limited research. This study examined the long-term psychosocial outcome of a large cohort of adult males born with hypospadias. The purpose of this case–control study was to assess a possible negative influence on the psychosocial outcome in adult males with hypospadias. Males with hypospadias treated in Sweden and aged ≥18 years old participated in this follow-up study. Age-matched men and university students were recruited as controls. The participants answered a questionnaire designed to reflect the subjective quality of life, social factors, need of support and follow-up, and the perceived impact of the disease upon upbringing. It also looked at the validated Psychological General Well-Being (PGWB) questionnaire and Relationship Questionnaire (RQ). A total of 167 patients (median age 34 years, 63% distal, 24% mid, and 13% proximal hypospadias) and 169 controls (median age 33 years) participated in the study. Patients had their first operation at 4 years of age (median) and the median follow-up time was 29 years following the first surgery. Men with hypospadias had a comparable total quality of life level with a mean total PGWB score of 82 (normal range 78–83) compared with 85.6 in controls. Scores on wellbeing and vitality were lower, even if the differences were small. Hypospadias did not affect marital status, presence of children in the family, frequency of employment or experience of bullying. These men more often lived at home with their parents (P=0.001) and had a lower level of education (P=0.004), even if the educational level in both patients and controls was high compared with the general Swedish population. Patients with proximal hypospadias were shorter compared with controls (P=0.003), which was consistent with the prenatal growth restriction associated with hypospadias. The group with proximal hypospadias expressed a greater need for medical (45.5%) follow-up compared with mid (28.2%) and distal (18.1%) cases (P=0.001). Patients with proximal hypospadias tended to avoid close relationships because of fear of being hurt. The findings suggested that patients treated for hypospadias have a good HRQoL, can be expected to have a normal psychosocial life, and marry and have children. Repeated follow-up and psychological support during childhood/adolescence is however of great importance for patients with more proximal hypospadias.Summary tableCharacteristics of study population and basic psychosocial data.Summary tablePatientsControlsNumber of casesNumber of controlsNumber (N)167169Age, years (Md)34 (SD 8)33 (SD 7)Hypospadias phenotypeDistal105 (63)–Mid40 (24)–Proximal22 (13)–Age at first surgery, years4 (0–21)–Follow-up time, years (Md)29 (6–48)–Chi-squared (Fisher's test*)N (%)N (%)P-valueMarried/co-habitantYes100 (60)106 (63)No67 (40)63 (35)0.593PartnerYes119 (72)123 (76)No47 (28)38 (24)0.332Biological childrenYes63 (38)58 (34)No104 (62)111 (66)0.131WorkingYes131 (78)128 (76)No36 (22)41 (24)0.556Signed off/disability pensionYes3 (2)0 (0)No36 (98)169 (100)0.122*University degreeYes72 (43)102 (60)No92 (55)64 (38)0.004–3 (2)3 (2)Living at home with parentsYes16 (10)2 (1)No151 (90)167 (99)0.001*Stature, cm (Md)IQRIQRControl–183 (10)–Distal183 (5)–1.000**Mid173 (10)–0.099** (P-value compared)Proximal158 (25)–0.029** (to controls)**P-value compared with controls.Values in bold indicate significant difference.The significance level is 0.05.IQR, interquartile range; Md, median; N, number.